2018
DOI: 10.3390/min8040130
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Cationic Polymer Adsorption on Mineral Surfaces: Kaolinite in Cement Aggregates

Abstract: Abstract:We present a joint experimental and theoretical investigation into the adsorption of polycationic quaternary ammonium polymers on the clay mineral kaolinite. Within the cement and concrete manufacturing industries such polymers are used to improve the final product by inerting the adsorption capacity of the clay minerals for more expensive additives. The adsorption of the presently used polymer (FL22) was compared with both a similar variant, but without a hydroxyl group (Fl22mod) and uncharged polyvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 46 publications
0
10
1
Order By: Relevance
“…Recent experimental results of zeta potential titration of kaolinite have shown dissociation of the kaolinite surface at neutral pH ( Jacquet et al, 2018 ). Then, at neutral pH some OH groups of kaolinite can be dissociated.…”
Section: Resultsmentioning
confidence: 99%
“…Recent experimental results of zeta potential titration of kaolinite have shown dissociation of the kaolinite surface at neutral pH ( Jacquet et al, 2018 ). Then, at neutral pH some OH groups of kaolinite can be dissociated.…”
Section: Resultsmentioning
confidence: 99%
“…Ashok Kumar 1 , Kaman Singh 1 * and Satya Prakash Gupta 2 1 Surface Science Laboratory, Department of Chemistry, Babasaheb Bhimrao Ambedkar University (A Central University), Lucknow, U.P., India 2 Prasad Polytechnic Lucknow, Sarai Sahjadi, Uttar Pradesh, India *Address all correspondence to: singh.kaman@bbau.ac.in; drkamansingh@yahoo.com Hydroxyethylcellulose (HEC) and its hydrophobically modified derivatives have been widely used in many industrial areas such as pharmaceuticals, cosmetics, textiles, paint and mineral industries including in oil extraction, coating, medication, food, and polymer polymerization. This was non-toxic and inexpensive.…”
Section: Author Detailsmentioning
confidence: 99%
“…Natural aggregates are still important in cement production, though high-purity sources are becoming harder to come by. The CDs have been used to "inert" the aggregate to the cement formulation to prevent clay minerals associated with the aggregates from adversely affecting the cement formulation by adsorption of plasticizers and resulting property alteration [2]. The CD's application in the upstream petroleum industry, such as exploration, drilling, development, and distribution, has recently sparked renewed interest.…”
Section: Introductionmentioning
confidence: 99%
“…Kashani et al [138] demonstrated that cationic polymers with long side chains gave enhanced yield stress reduction compared with the anionic equivalent in AAGBS. Although most cationic polymers have been developed for adsorption onto clay surfaces at lower pH [146], there is an opportunity to develop cationic copolymers for plasticising AAM with higher silicate addition.…”
Section: Surface Chemistry and Plasticising Admixturesmentioning
confidence: 99%